Cultural Conflicts in Jhumpa Lahiri’s Interpreter of Maladies - K. Balaji Sundharam, (The Creative Launcher, 2018)
Interpreter of Maladies is an accumulation of nine short stories embodied characters of Indian drop living in the United States. There is a collection of plots inside of the accumulation that portrays a various society of immigrants. For example, the stories' characters range from kids attempting to comprehend their home lives versus their school lives, to youthful grown-ups uncertain of being American and their association with their legacy, lastly more seasoned grown-ups who constantly battle to acknowledge their new lives and overlook their old. These characters respond distinctively to their family, companions, and foes, containing an impartial outline of how fluctuated India foreigners 'identities are in spite of their regular ethnic foundation. It endeavours to smash past by concentrating on a wide range of characters, places, and plots inside of the same verifiable and social setting. Jhumpa Lahiri couldn't get away from her legacy, in light of the fact that it is inside of her hereditary material.